Principal’s Leadership At SMP Daarul Qur’an Ungaran Central Java - Ariyantho, Ariyantho; Raharjo, Tri Joko; Prihatin, Titi (Educational Management, 2021)
Education in Indonesia plays an important role in nation-building, particularly its people. Schools’ success is very much dependent on that of their principals in exercising their roles and performing tasks. One of the decisive factors which the quality of education and school effectivity depend on is a principal’s leadership. The purpose of this research is to analyze the school principal’s leadership at SMP Daarul Qur’an Ungaran, Central Java. This is a descriptive and qualitative research employing study-case approach. Using purposive sampling, the respondents of this research are the school principal, teachers and school committee. The collection of data was carried out by interview, observation and documents study using source triangulation as the technique to ensure their validity. The data were then analyzed by utilizing data reduction, data display and verification or inference. The result of the research shows that the principal is able to fulfill his tasks and responsibilities as the leader at SMP Daarul Qur’an Ungaran, Central Java, promoting democratic leadership. The leadership of SMP Daarul Qur’an principal has been highly regarded by his subordinates (teachers, staff and students alike). The school principal is constantly attempting to improve the quality of the service in place, both the academic and religious aspects, so as to uphold its position as an Islamic education institution by maintaining religious values in learning process at SMP Daarul Qur’an. The success and effectivity of SMP Daarul Qur’an principal’s leadership take shape in his quotidian attitude, delegation of tasks, decision making, supervision, school development, communication, motivational speech and provision of rewards to his subordinates. Keywords: Leadership, School Principal, SMP Daarul Qur’an